Identifying listening problems and the need for technology assisted language learning (TALL) to improve listening skills among diploma students / Salwani Mohd Salleh ... [et al.] - Mohd Salleh, Salwani; May, Lai See; Azmi, Azzieatul Syazwanie; Mohd Hatta, Siti Anisah; Razali, Norlida; Mohd Zawawi, Mohd Zafian (Universiti Teknologi MARA, 2018)
Listening is one of the major skills in English language acquisition. However, mastering listening in acquiring the language can be challenging. Failure to listen well may cause misunderstanding and unnecessary conflicts. Realizing the importance of listening and how difficult it is, the paper focuses on listening issues experienced by 210 Part 1, Diploma students of UiTM Kelantan Branch. The objectives are to identify the perceived level of listening proficiency among students, ascertain listening problems faced by them and determine students' need for Technology Assisted Language Learning (TALL) to enhance listening skills. Thus, a survey on listening problems and the need for TALL was conducted. 150 students responded and the majority identified physical setting as the main listening problem thus, leading to a conclusive need for technology to help improve their listening ability. Based on the findings, a technological language tool in the form of multimedia application is innovated to fulfil the students' needs. The application is designed to be easily accessible, user-interactive, user-friendly and affordable. The features are customized to be as 'friendly' as possible of which they include local and Malaysian-based contents, familiar accents and slangs as well as relevant vocabulary, listening practices and quizzes.